2003
DOI: 10.1590/s1516-31802003000500003
|View full text |Cite
|
Sign up to set email alerts
|

Role of video-assisted thoracoscopic sympathectomy in the treatment of primary hyperhidrosis

Abstract: CONTEXT: Essential hyperhidrosis is a frequent disorder causing significant functional impairment. The advent and development of video-assisted thoracoscopic techniques now allows thoracic sympathectomy to be carried out precisely and safety with good results and minimal morbidity. OBJECTIVE: To assess the impact of video-assisted thoracic sympathectomy in patients diagnosed as presenting severe and disabling hyperhidrosis. TYPE OF STUDY: This was a longitudinal study of the clinical course of all hyperhidrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 20 publications
1
42
1
6
Order By: Relevance
“…In previous studies, postoperative pain was reported between 0.8 and 93 % for thoracoscopic surgeries [2,10,11,13,[17][18][19]. Pain at the time of discharge affected 20 % of the patients, which decreased to 10 % at the tenth day of postoperation in our study.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In previous studies, postoperative pain was reported between 0.8 and 93 % for thoracoscopic surgeries [2,10,11,13,[17][18][19]. Pain at the time of discharge affected 20 % of the patients, which decreased to 10 % at the tenth day of postoperation in our study.…”
Section: Discussionsupporting
confidence: 53%
“…Palmar hyperhidrosis is a relatively frequent situation, which causes social embarrassment, psychological problems, and interruption in daily activities [5,[9][10][11]. Although nonoperative treatment modalities such as topical agents, iontophoresis, antidepressants, and botox may provide some benefits, they have short effect duration and some side effects [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of permanent Horner's syndrome was 0.3%, probably induced by misidentification of the T2 ganglion, excessive traction on the chain or excessive use of diathermy. Another problem arising during thoracoscopic sympathectomy is that of postoperative pain requiring opioid analgesia [25] or tricyclic antidepressants [26]. None of the above events was found during our CT-guided method.…”
Section: Discussionmentioning
confidence: 79%
“…(4) The authors of the aforementioned Editorial cited recidivism rates of 8.2% for palmar hyperhidrosis and 13% for axillary hyperhidrosis. (2,5) Finally, it is of note that we carried out between 3 and 10 sympathectomies per week and always taught our graduate students and residents that professional and scientific ethics are incompatible with deviations.…”
mentioning
confidence: 99%